1993
DOI: 10.1152/jappl.1993.74.6.2795
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and renal effects of hypoxia in conscious carotid body-denervated rats

Abstract: The contribution of peripheral arterial chemoreceptors to cardiovascular and renal responses to acute hypocapnic hypoxia is currently not well understood. We compared the effects of normobaric hypoxia on mean arterial blood pressure (MABP), heart rate, glomerular filtration rate (GFR), renal blood flow (RBF), and renal volume and electrolyte excretion in conscious unilaterally nephrectomized carotid body-denervated (n = 10) and sham-operated (n = 10) control rats. Thirty minutes of normobaric hypoxia (12.5% O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
4
12
0
Order By: Relevance
“…The respiratory, cardiovascular and renal responses induced in the rat by moderate hypoxia in the present study were comparable with those we reported recently (Neylon et al 1995 (Behm, Mewes, DeMuinck Keizer, Unger & Rettig, 1993). The present study provided the additional information that moderate hypoxia was accompanied by a 2-8-fold increase in plasma renin activity as might be explained by the reflex response to peripheral chemoreceptor stimulation, baroreceptor unloading and the fall in RPP (see the introduction, and below).…”
Section: Discussionsupporting
confidence: 92%
“…The respiratory, cardiovascular and renal responses induced in the rat by moderate hypoxia in the present study were comparable with those we reported recently (Neylon et al 1995 (Behm, Mewes, DeMuinck Keizer, Unger & Rettig, 1993). The present study provided the additional information that moderate hypoxia was accompanied by a 2-8-fold increase in plasma renin activity as might be explained by the reflex response to peripheral chemoreceptor stimulation, baroreceptor unloading and the fall in RPP (see the introduction, and below).…”
Section: Discussionsupporting
confidence: 92%
“…It is notable that the changes in Pa.O2 and Pa,co2 recorded during the present study were very similar to those reported by Behm et al (1993) in unanaesthetized rats subjected to a 30 min period of breathing 125% 02. However, the fall in ABP in the unanaesthetized rats was substantially smaller in absolute and percentage terms.…”
Section: Respiratory and Systemic Cardiovascular Changessupporting
confidence: 91%
“…In humans, for example, hypoxia has been reported to cause diuresis and natriuresis [34] or to cause antidiuresis and antinatriuresis [35]. Similarly, in rats, diuresis and natriuresis [36] or antidiuresis and antinatriuresis [37] have been described. However, more recent evidence suggests that acute hypoxia in rats causes antidiuresis and antinatriuresis [38,39] and that chronic hypoxia results in normal renal function [40].…”
Section: Discussionmentioning
confidence: 99%